Forensic analytics using cluster analysis: Detecting anomalies in data - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2021)
Cluster analysis is a data analytics technique that can help forensic accountants effectively detect anomalies in complex financial datasets. This article provides a description of clustering analysis, discusses how it can be implemented to detect anomalies in data, and illustrates its use through a worked example using the Tableau software.